Sciatic Nerve Palsy following Curved Periacetabular Osteotomy - Masahiro Fujita; Shinya Hayashi; Kenichi Kikuchi; Yoshinori Takashima; Tomoyuki Kamenaga; Masanori Tsubosaka; Koji Fukuda; Koji Takayama; Shingo Hashimoto; Takahiro Niikura; Ryosuke Kuroda; Tomoyuki Matsumoto (Case Reports in Orthopedics)
Curved periacetabular osteotomy (CPO) is used for the treatment of dysplastic hips. Previous studies have reported satisfying outcomes and low rate of severe complications associated with this procedure; however, no case of postoperative sciatic nerve palsy has been reported. In this study, we describe a case of postoperative sciatic nerve palsy following CPO due to nerve strangulation by scar tissue without direct injury. A female patient had severe buttock pain and posterior leg numbness after she underwent left-side CPO. Postoperative magnetic resonance imaging showed that the sciatic nerve was strangulated by the surrounding soft tissue. There was no bone fragment, active infection, bone necrosis, tumor, or spine disease. Therefore, we diagnosed nerve palsy by soft tissue strangulation, and revision surgery was indicated. During revision surgery, the sciatic nerve was observed to be strangulated by the scarring soft tissue, and the nerve had no mobility. After detachment, the pain and numbness disappeared. Direct injury of the sciatic nerve should not be caused by CPO; however, there is a possibility of postoperative sciatic nerve palsy due to the scarring soft tissue. Early diagnosis and appropriate treatment are important for optimal postoperative clinical outcomes.